2020
DOI: 10.3390/cells9122655
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+ Dyshomeostasis Disrupts Neuronal and Synaptic Function in Alzheimer’s Disease

Abstract: Ca2+ homeostasis is essential for multiple neuronal functions and thus, Ca2+ dyshomeostasis can lead to widespread impairment of cellular and synaptic signaling, subsequently contributing to dementia and Alzheimer’s disease (AD). While numerous studies implicate Ca2+ mishandling in AD, the cellular basis for loss of cognitive function remains under investigation. The process of synaptic degradation and degeneration in AD is slow, and constitutes a series of maladaptive processes each contributing to a further … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 243 publications
(198 reference statements)
1
32
0
Order By: Relevance
“…With continuous studies, it is considered that the main pathogenesis of AD includes the degeneration of Aβ [90][91][92], hyperphosphorylation of Tau protein [93], the imbalance of choline [94], neuroinflammation [95,96], abnormalities in neurotransmitters, and dysfunction of mitochondrial autophagy [97,98]. In addition, recent studies have revealed that gut microbiota dysregulation [99,100] and Ca2+ influx [101,102] are also closely associated with AD.…”
Section: 2mentioning
confidence: 99%
“…With continuous studies, it is considered that the main pathogenesis of AD includes the degeneration of Aβ [90][91][92], hyperphosphorylation of Tau protein [93], the imbalance of choline [94], neuroinflammation [95,96], abnormalities in neurotransmitters, and dysfunction of mitochondrial autophagy [97,98]. In addition, recent studies have revealed that gut microbiota dysregulation [99,100] and Ca2+ influx [101,102] are also closely associated with AD.…”
Section: 2mentioning
confidence: 99%
“…It is characterized by extracellular accumulation of amyloid plaques and intraneuronal tau neurofibrillary tangles causing loss of synapses and synaptic plasticity, thus impairing learning and memory [2][3][4][5]. It is further known that alterations in the homeostasis of glutamate and other ions such as Ca 2+ are involved in the pathogenesis of AD [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Aβ cascades have been proposed as triggers for excitotoxity in AD. [51][52][53] The proposition, however, cannot account for how neurodegeneration could develop before Aβ-related pathologies in many AD cases. Our investigation is an initial effort to reveal the primary pathogenic mechanism mediated by continual hyperactivities of NMDAR in the deficiency of its unique inhibitory subunit GluN3A.…”
Section: Historical Evolution and Updated Hypothesismentioning
confidence: 99%